Influence of longitudinal magnetic field in the MPC channel on the density of generated plasma stream - Marchenko, A.K.; Byrka, O.V.; Makhlai, V.A.; Herashenko, S.S.; Solyakov, D.G.; Volkova, Y.E.; Yeliseyev, D.V.; Novakowska-Langier, K. (Вопросы атомной науки и техники, 2021)
The paper is devoted to experimental measurements and analysis of parameters of the plasma streams generated by magnetoplasma compressor (MPC) upgraded with an external axial magnetic field. Influence of the external axial magnetic field of 0.24 T on helium plasma streams (P=2 Torr) has been studied. The measurements of average electron density distributions were performedboth with and without an external axial B-field. Distributions of plasma electron density Ne (L) were measured with spectroscopy in the plasma stream and in the compression zone using Stark broadening of He I and He II spectral lines. Plasma-surface interaction processes were also analyzed.